MEMBANGUN KESADARAN DEMOKRASI MENJELANGPILGUB DKI JAKARTA BAGI GENERASI MUDA (Lembaga Penerbitan Universitas Esa Unggul, 2016)
AbstractDemocracy as a modern system of government. In the implementation of democracy often leads to lack of achievement of objectives, namely the State's prosperity and the nation's intelligence, political system of Pancasila democracy is a political system that is constitutional. The political system of Pancasila democracy should not only be reflected in the various activities of government and state, but must also be reflected in the social life of Indonesian citizens everyday, the process of democratization in Indonesia at the local level are marked with the recruitment process of regional heads submitted directly to the people with the hope of being able provide material corrections to the abuses of democratic practice in the past, the embodiment of the elections directly, local governance and political institutions of local (DPRD) can cooperate in accordance with the expectations of the people, an area will get a head area of a reliable, competent and have high integrity building area, local elections Concurrent has benefits, including budget efficiency and effectiveness of electoral institutions. Keywords: awareness, democracy, youths AbstrakDemokrasi sebagai sistem pemerintahan negara modern. Dalam implementasinya demokrasi sering kurang mengarah tercapainya tujuan Negara yaitu kemakmuran dan kecerdasan bangsa, Sistem politik demokrasi Pancasila merupakan sistem politik yang konstitusional. Sistem politik demokrasi Pancasila tidak hanya harus tercermin dalam berbagai kegiatan pemerintahan dan kenegaraan, tetapi harus juga tercermin dalam kehidupan bermasyarakat warga Negara Indonesia sehari-hari, proses demokratisasi di Indonesia di tingkat lokal ditandai dengan proses rekrutmen kepala daerah diserahkan secara langsung kepada rakyatdengan harapan mampu memberikan bahan koreksi terhadap penyelewengan praktik demokrasi dimasa lalu,perwujudan Pilkada langsung, tata pemerintahan daerah dan institusi politik lokal (DPRD) dapat bekerja sama sesuai dengan harapan rakyat, suatu daerah akan mendapatkan kepala daerah yang handal, kompeten dan mempunyai integritas tinggi membangun daerah, pilkada serentak memiliki manfaat, diantaranya efisiensi anggaran danefektivitas lembaga pemilihan umum. Kata kunci: kesadaran, demokrasi, generasi muda